THE ROLE OF THE SECURITY INTELLIGENCE UNIT (SAT INTELKAM) OF THE SABANG POLICE IN CARRYING OUT SUPERVISION AND CONTROL OF FIREARMS NON-ORGANIC POLRI/TNI IN SABANG CITY - Muhammad Hidayat Robby; Danial Syah; Indra Gunawan Purba (Jurnal Ilmiah METADATA, 2026)
The possession of illegal firearms is not only seen as a form of violation of the law, but also as a means of dangerous crime by the perpetrators of criminal acts. The legal regulation of the use of non-organic firearms by the National Police/TNI in Indonesia is regulated in the National Police Regulation of the Republic of Indonesia (Perpol) No. 1 of 2022,. The role of the Security Intelligence Unit (Sat Intelkam) of the Sabang City Resort Police in supervising and controlling non-organic firearms of the National Police/TNI is to supervise and control non-organic firearms of the National Police/TNI which aims to ensure that the use of firearms is carried out in accordance with applicable regulations, prevent misuse, and maintain security and order.